Response Predictors of Repetitive Neuromuscular Magnetic Stimulation in the Preventive Treatment of Episodic Migraine - Börner, Corinna; Renner, Tabea; Trepte-Freisleder, Florian; Urban, Giada; Schandelmaier, Paul; Lang, Magdalena; Lechner, Matthias F.; Koenig, Helene; Klose, Birgit; Albers, Lucia; Krieg, Sandro M.; Baum, Thomas; et al. (Frontiers in Neurology, 2022)
Background: Repetitive neuromuscular magnetic stimulation (rNMS) of the trapezius muscles showed beneficial effects in preventing episodic migraine. However, clinical characteristics that predict a favorable response to rNMS are unknown. The objective of this analysis is to identify such predictors. Methods: Thirty participants with a diagnosis of episodic migraine (mean age: 24.8 ± 4.0 years, 29 females), who were prospectively enrolled in two non-sham-controlled studies evaluating the effects of rNMS were analyzed. In these studies on the effects of rNMS, the interventional stimulation of the bilateral trapezius muscles (six sessions distributed over two consecutive weeks) was surrounded by 30-days baseline and follow-up periods. Baseline and follow-up assessments included the continuous documentation of a headache calendar over 30 days before and after the stimulation period, the Migraine Disability Assessment Score (MIDAS) questionnaire (before stimulation and 30 days after stimulation), and measurements of pain pressure thresholds (PPTs) above the trapezius muscles by algometry (before and after each stimulation session). Participants were classified as responders based on a ≥25% reduction in the variable of interest (headache frequency, headache intensity, days with analgesic intake, MIDAS score, left-sided PPTs, right-sided PPTs). Post-hoc univariate and multivariate binary logistic regression analyses were performed. Results: Lower headache frequency (p=0.016) and intensity at baseline (p=0.015) and a migraine diagnosis without a concurrent tension-type headache component (p=0.011) were significantly related to a ≥25% reduction in headache frequency. Higher headache frequency (p=0.052) and intensity at baseline (p=0.014) were significantly associated with a ≥25% reduction in monthly days with analgesic intake. Lower right-sided PPTs at baseline were significantly related to a ≥25% increase in right-sided PPTs (p=0.0.015) and left-sided PPTs (p=0.030). Performance of rNMS with higher stimulation intensities was significantly associated with a ≥25% reduction in headache intensity (p=0.046). Conclusions: Clinical headache characteristics at baseline, the level of muscular hyperalgesia, and stimulation intensity may inform about how well an individual patient responds to rNMS. These factors may allow an early identification of patients that would most likely benefit from rNMS.